Moenkhausia celibela: a new species from the Amazon basin, Brazil (Characiformes: Characidae) - Marinho, M. M. F.; Langeani, Francisco [UNESP] (Wiley-Blackwell, 2010)
A new species of Characidae, Moenkhausia celibela, is described from the Rio Amazonas at Santarem, Rio Marau, several localities in the Rio Tapajos, Rio Curua-Una, Rio Xingu and Rio Jari, all from the Amazon basin, Brazil. The new species is distinguished from its congeners, except species included in Gery's 1992 Moenkhausia lepidura group, by presenting a dark blotch on the upper caudal-fin lobe, and the lower lobe is hyaline or light grey. Moenkhausia celibela is distinguished from the species of the M. lepidura group by the absence of a humeral spot and the presence of a roughly triangular and dark spot at the caudal-fin base, extending posteriorly along the middle caudal-fin rays, and distinctly separate from the spot on the upper caudal-fin lobe.
Keywords: Fresh water; Moenkhausia lepidura; Neotropic; South American